If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5g + -4) = 0 Reorder the terms: -3(-4 + 5g) = 0 (-4 * -3 + 5g * -3) = 0 (12 + -15g) = 0 Solving 12 + -15g = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -15g = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -15g = 0 + -12 -15g = 0 + -12 Combine like terms: 0 + -12 = -12 -15g = -12 Divide each side by '-15'. g = 0.8 Simplifying g = 0.8
| 9+4z=1-2z | | 2x^3=7x-5 | | -9y^2+8y^2+y^2= | | 3x-6=5(x+2) | | 90-30=2x | | -2u+5(u+7)=11 | | (5t-1)(3t-2)= | | 4/8-(2/16)= | | 6x7-8/4 | | 15c=12+.99 | | Ln(x-6)+ln(x+1)=ln(x-5) | | 8(v-5)+8v=24 | | f^1(x)=sin(9x) | | 4(-2g+5)= | | -5x-186=7x+78 | | 2x+79=7x+14 | | 50*80/100 | | 2(w+7)+5w=-21 | | 4w-53+5w=73+11w | | (m^2+9)(m-3)= | | 4/8-2/16 | | x+-8=-52 | | 9x-17=7x+19 | | 3(t+16)+t=109 | | 22=-1(y+7) | | (X-10)^2/5=(9x)1/5 | | 4+8+9(3a+5)+8(2+1)= | | 7(3x-5)=5(4x-5) | | 20x+20x=140 | | 600(-2)+200=500(-2) | | 3(7x-5)=4(3x-11) | | 2(e-30)+2e=135 |